Biometric approximation of diaphragmatic contractility during sustained hyperpnea - Kabitz, Hans-Joachim; Walker, David Johannes; Schwoerer, Anja; Schlager, Daniel; Walterspacher, Stephan; Storre, Jan Hendrik; Roecker, Kai; Windisch, Wolfram; Vergès, Samuel; Spengler, Christina M. (Respiratory physiology & neurobiology, 2011)
Imposing load on respiratory muscles results in a loss of diaphragmatic contractility that develops early, is independent of task failure, and levels off following the initial decrease. This study assessed the progression of diaphragmatic contractility during sustained normocapnic hyperpnea and applied a biometric approximation (hypothesis: non-linear decay). Ten healthy subjects performed three consecutive hyperpnea bouts (I:6 min warm up/II:9 min/III:task failure 28.6 ± 11.5 min; mean ± SD) at maximal voluntary ventilation fractions (I:30–60%/II:70%/III:70%), followed by recovery periods (I:18 min/II:6 min/III:30 min). Twitch transdiaphragmatic pressure (TwPdi) was assessed throughout the protocol. Bouts II and III induced diaphragmatic fatigue (TwPdi baseline vs. Recovery −19 ± 17% and −30 ± 16%, both p < 0.05 RM-ANOVA) while bout I did not. During sustained hyperpnea (II/III), TwPdi followed an exponential decay ( r 2 = 0.91). The reduction in diaphragmatic contractility closely follows a non-linear function with an early loss in diaphragmatic contractility during sustained hyperpnea, levels off thereafter, and is independent of task failure. Thus, reasons other than diaphragmatic fatigue are likely to be responsible for task failure during sustained hyperpnea.